Cholestatic hepatitis in a patient with typhoid fever - a case report - Wijesiriwardena Bandula C; Shivanthan Chrishan; Ratnayake Eranda C (BMC, 2011)
Abstract Typhoid fever is a very common infectious disease, particularly in developing countries such as Sri Lanka. Although multiple organs are known to be affected by the disease, hepatic involvement could be considered the most important as studies have showed that it is associated with a higher relapse rate. We report a young patient who presented with fever and jaundice and found to have cholestatic hepatitis secondary to typhoid fever.